Prediction of flexural drift capacity in masonry walls through a nonlinear truss-based model. (15th May 2022) - D'Altri, A.M.; de Miranda, S.
Graphical abstract: Abstract: In this paper, the in-plane flexural drift capacity of masonry walls is numerically investigated. In particular, a nonlinear truss-based model is specifically developed to predict the monotonic response of in-plane horizontally-loaded masonry walls undergoing flexural failure, so that to investigate their deformation capacity. This novel modelling strategy assumes a band of nonlinear truss elements at the wall toe to account for flexural failure. The truss elements are supposed no-tension with plastic-softening behaviour in compression. This simple and original model is easily and fully characterizable by experimentally-based compressive stress–strain relationships available in the literature for different masonry types. The modelling strategy is validated against two different pier-scale experimental tests which experienced flexural failure. The model is then used to predict the flexural drift capacity of walls with different masonry types and geometrical features, subjected to a full-range of axial load ratios. As a result, drift capacity is found to nonlinearly decrease while increasing the axial load ratio, and to be sensibly dependent on the wall width (i.e. drift capacity diminishes while increasing wall width), for any masonry type. Finally, a simple analytic expression based on numerical results is deduced for the flexural drift capacity of masonry walls, function of axial load ratio, masonry type, and wall size. Accordingly, this analytic expression could be implemented in any structural analysis masonry-oriented commercial code to account for a consistent description of the flexural drift capacity of masonry walls.